A Comparative Evaluation of Dexamethasone and Tramadol as Adjuvant to Levobupivacaine in Supraclavicular Block - Rangit Priyakar Pandey; Richa Chandra (Academia Anesthesiologica International, 2020)
Background: The present study was conducted to evaluate and compare dexamethasone and tramadol as adjuvant to levobupivacaine in supraclavicular block. Subjects and Methods: The present study was conducted on 50 patients of American Society of Anesthesiologists (ASA) grade I and II. Patients were divided in to two groups of 25 each. In group I, 30 ml of 0.5% levobupivacaine hydrochloride plus 2 ml tramadol (100 mg) was used. In group II, 30 ml of 0.5% levobupivacaine hydrochloride plus 2 ml dexamethasone (8 mg) was used. Visual Analogue Scale was used. The onset of sensory and motor block was evaluated.Results: The mean onset of sensory block in group I was 5.41 minutes and in group II was 3.86 minutes, motor onset was 9.12 minutes in group I and 7.25 minutes in group II, duration of sensory block in group I was 12.14 hours and in group II was 15.34 hours, duration of motor block in group I was 14.34 hours and I group II was 16.23 hours, duration of analgesia in group I was 16.1 hour and in group II was 18.4 hours. The difference was significant difference (P<0.05). The mean VAS score in group II was better as compared to group I (P <0.05). Conclusion:Authors found that dexamethasone is a better adjuvant than tramadol when added to levobupivacaine in supraclavicular brachial plexus block.